Spawning phenology of a rapidly shifting marine fish species throughout its range. (25th January 2021) - Slesinger, Emily; Jensen, Olaf P; Saba, Grace
Abstract: Ocean warming is leading to poleward range shifts for many fish species, and while well described, potential life history phenology differences within fish populations along a gradient from their historic to current distributional range have not been studied. In a rapidly shifting fish population, the Northern stock of black sea bass ( Centropristis striata ), we investigated spawning phenology and output across the US Northeast Shelf to comprise locations in their historic and more recently occupied range near their northern range boundary. Spawning started later in the northern extreme of our study but also ended earlier, leading to decreased spawning duration from south to north. Spawning phenology was mostly driven by Julian day followed by temperature and latitude. Gonadosomatic index, a proxy for reproductive output, was lower in the northern region, indicating that black sea bass did not compensate for the shorter spawning season there. Hepatosomatic index was lower in the northern regions indicating lower pre-spawning liver energy reserves, potentially leading to lower reproductive output. These results suggest a potential for lower recruitment in the recently occupied range and should be further investigated to predict the impacts of ocean warming and for proactive fisheries management as black sea bass distributional range expands poleward.